2004
DOI: 10.2135/cropsci2004.1721
|View full text |Cite
|
Sign up to set email alerts
|

Kentucky Bluegrass Response to Potassium and Nitrogen Fertilization

Abstract: The response of Kentucky bluegrass (Poa pratensis L.) to potassium (K) fertilization has been inconsistent. The objective of this research was to determine the effects of K fertilization across varying nitrogen (N) rates and clipping management on Kentucky bluegrass clipping yields, quality, tissue K concentrations, apparent N recovery, and N use efficiency. A 2 × 4 × 4 factorial was arranged in a split‐plot design and repeated across two years. Main plots were clipping treatments (returned vs. removed) and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 33 publications
2
32
1
Order By: Relevance
“…3A). This trend is in agreement with studies that found increasing N uptake with increasing rates of N application (Kopp and Guillard, 2002a;Fitzpatrick and Guillard, 2004). Apparent N recovery ranged from 28 to 40% of applied N, with a maximum corresponding to 4.7 μg cm −2 d −1 AEM soil NO 3 -N (Fig.…”
Section: Nitrogen Uptake Recovery and Use Effi Ciencysupporting
confidence: 92%
See 1 more Smart Citation
“…3A). This trend is in agreement with studies that found increasing N uptake with increasing rates of N application (Kopp and Guillard, 2002a;Fitzpatrick and Guillard, 2004). Apparent N recovery ranged from 28 to 40% of applied N, with a maximum corresponding to 4.7 μg cm −2 d −1 AEM soil NO 3 -N (Fig.…”
Section: Nitrogen Uptake Recovery and Use Effi Ciencysupporting
confidence: 92%
“…A decrease in apparent N recovery at higher N fertilizer application rates has been noted in cool-season mixed species turfs (Kopp and Guillard, 2002a;Fitzpatrick and Guillard, 2004) and in sandbased creeping bentgrass (Agrostis stolonifera L.) turfs (Huang and Petrovic, 1994). This effect has been noted also in orchardgrass (Dactylis glomerata L.), tall fescue (Festuca arundinacea Schreb.…”
mentioning
confidence: 83%
“…The responses presumably plateau once physiological requirements for the nutrients are satisfied at the prevailing growth ISRN Agronomy rates. This may well explain why there is no luxury uptake of K by turfgrass [29] and that uptakes of K, Ca, and Mg reflect their physiological requirements rather than their ratios on soil cation exchange sites [27]. Turfgrass clipping nutrient content has been reported to change significantly over the course of a growing season even when nutrient supply is more than adequate.…”
Section: Consequences Of Turfgrass Nutrientmentioning
confidence: 99%
“…Variable nutrient demand at a fixed soil supply may account for difficulties encountered in soil test calibrations and interpretations for turfgrass [23], for reported differences in turfgrass species and cultivar nutrient requirements and nutrient use efficiencies [24][25][26], for lack of relationships between tissue cation and soil exchangeable cation concentrations [27,28], and for lack of K luxury consumption by turfgrass [29].…”
Section: Introductionmentioning
confidence: 99%
“…The prediction of yield response to K fertilizer applications based on soil tests for exchangeable K is sometimes of limited accuracy (Pal et al, 2001), particularly for perennial crops such as coffee. The K uptake from nonexchangeable forms by plants has been described (Fitzpatrick & Guillard, 2004) and several mineralogical studies confirmed great differences among soils concerning the K-supply potential.…”
Section: Introductionmentioning
confidence: 97%